The role of life context and self‐defined well‐being in the outcomes that matter to people with a diagnosis of schizophrenia. (3rd April 2017) - Lloyd, Helen; Lloyd, Joanne; Fitzpatrick, Ray; Peters, Michele
Abstract: Objective: Conduct a deep exploration of the outcomes that matter to people with a diagnosis of schizophrenia and understand from their perspective how these outcomes can be achieved. Sample and Methods: In‐depth qualitative interviews were conducted with 22 people with a diagnosis of schizophrenia. Interviews were analysed using thematic frameworks, and a realist informed theories of change approach. Results: Our study revealed the potential causal relationships between the context of a person's life, short‐term goals and long‐term outcomes. We provide a nuanced and detailed exploration of outcomes that matter for people with schizophrenia in relation to self‐defined well‐being. Achieving life milestones, feeling safe and outcomes related to improved physical health along with employment, a positive sense of self and psychosocial outcomes, were highly valued. For short‐ and long‐term outcomes to be achieved, individuals required medication with minimal side‐effects, cognitive behavioural therapy, family/social support and meaningful activities in their lives. Well‐being was influenced by life context and short‐ and long‐term outcomes, but in a circular nature also framed what short‐term goals could be achieved. Conclusions: Working with people with a diagnosis of schizophrenia to identify and achieve better outcomes will necessitate a person‐centred approach. This will require an appreciation of the relationship between the statutory and non‐statutory resources that are available and a consideration of an individual's current well‐being status. This approach acknowledges personal strengths and encourages ownership of goals and supports self‐management.